Development of an FPGA-based real-time power system simulator for traveling wave-based protective relay validation - Leal, Marcos Sérgio Rodrigues (2019)
In this work a real-time digital simulator of power systems is implemented using a low-cost custom platform based on FPGA (field-programmable gate array) proper to perform real-time validation of traveling-wave-based transmission line protections. The operational view of the simulator is introduced by means of the modeling, implementation, and simulation steps of a transmission system, which is used to highlight the simulator capability to represent high-frequency transient phenomenon taking place transmission lines. Hence, at first, the mathematical models of the power system used in the case study are presented as well as the solver design, which is developed based on the electromagnetic transients program (EMTP). Then, the simulator characteristics, such as the hardware architecture, development software, communication strategies, graphical interface, input/output, and data export, are introduced, as well as the implementation stages of the test system. Moreover, it addresses the implementation of a relay prototype using a hardware based on DSP (digital signal processor), running an existing traveling-wavebased protection scheme, besides its closed-loop integration with the simulation. A GUI (graphical user interface) is developed to set the simulation parameters, including the conditions for applying an electrical fault, and to monitor the dynamic of the power system used as a case study. Off-line simulations obtained from Matlab/Simulink are used to validate the real-time results.